Intelligent buildings design, management and operation - Clements-Croome, Derek (Thomas Telford, 2004)
Intelligent buildings provide stimulating environments for people to work and live in. This book brings together a body of the latest knowledge about design, management, technology and sustainability set against the background of developments in the cultural landscapes, which affect those living and working in buildings.